Peran Bank NTT dalam Meningkatkan Motivasi Menabung Dikalangan Pelajar SMAS Katolik Regina Pacis Bajawa - Kawe, Finsensa W. Y. Moi; Bolla, Larasati V.; Loe, Stefanie Priska Mali (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to analyze the role of Bank NTT in improving the learning motivation of students at Regina Pacis Bajawa Catholic High School. This research method uses a qualitative and descriptive approach through direct observation and interviews with Bank NTT. Bank NTT programs, such as scholarships, financial management training, motivational seminars, and extracurricular collaboration with schools, are thought to have a significant contribution to increasing student motivation and achievement. The results of the study indicate that these programs not only increase students' awareness of the importance of financial education and literacy, but also build self-confidence and a spirit of achievement. Collaboration in extracurricular activities creates a positive and conducive learning atmosphere. In conclusion, Bank NTT plays a strategic role as an educational partner that contributes to creating a quality young generation. This study emphasizes the importance of synergy between the financial and education sectors to support the development of superior human resources.